2013
DOI: 10.1373/clinchem.2013.204099
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of 25 Leukemia-Associated Genes in a Single Work Flow by Next-Generation Sequencing Technology with Low Amounts of Input Template DNA

Abstract: BACKGROUND:We sought to establish a convenient, sensitive next-generation sequencing (NGS) method for genotyping the 26 most commonly mutated leukemiaassociated genes in a single work flow and to optimize this method for low amounts of input template DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These concordant results demonstrate the robustness of the amplified DNA, at the time of initial screening, as it not only enabled almost indefinite amplification of the ALL diagnostic samples, but also reproduced a faithful copy without the addition of further mutations, which would have made the analysis unacceptable. Similar results were recently obtained in a small cohort of 10 chronic myelomonocytic leukaemia patients, where the amplification technique was used with the aim of genotyping 25 leukaemia-associated genes despite the low amounts of DNA available (Rinke et al, 2013). In our study, the RQ-PCR results showed equivalent sensitivity levels.…”
Section: Discussionsupporting
confidence: 89%
“…These concordant results demonstrate the robustness of the amplified DNA, at the time of initial screening, as it not only enabled almost indefinite amplification of the ALL diagnostic samples, but also reproduced a faithful copy without the addition of further mutations, which would have made the analysis unacceptable. Similar results were recently obtained in a small cohort of 10 chronic myelomonocytic leukaemia patients, where the amplification technique was used with the aim of genotyping 25 leukaemia-associated genes despite the low amounts of DNA available (Rinke et al, 2013). In our study, the RQ-PCR results showed equivalent sensitivity levels.…”
Section: Discussionsupporting
confidence: 89%
“…NGS, including data analysis was performed for 30 leukemia-associated target genes on the 454 GS Junior platform with 454 GS Junior Titanium chemistry for amplicon sequencing (Roche Diagnostics, Basel, Switzerland) as previously described. 13,14 In total, amplicons were prepared for each sample and processed in a single NGS run. Mutations with a frequency >15% were confirmed using Sanger Sequencing with standard techniques on an ABI 3500 Genetic Analyzer (Thermo Fisher Scientific, Waltham, MA, USA) as described previously.…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%
“…15 To check the specific mutational status of individual colonies, Sanger sequencing of PCR products covering the relevant genetic regions was performed according to standard techniques. 14 Mutational analysis was performed using the Mutation Surveyor Software (SoftGenetics, State College, PA, USA). A dropping factor (drop in height of the normal peak at the position of the mutation relative to the neighboring peaks) of <30% was considered indicative of wild type, a dropping factor between 30% and 70% was considered to be a heterozygous mutation and a factor >70% was considered to be homozygous.…”
Section: Colony Assays and Sanger Sequencingmentioning
confidence: 99%
“…Though these and related alterations participate in the diagnosis and prognosis they remain insufficient to physio-pathological processes [12]. The introduction of novel diagnostic tools, such as high resolution karyo typing or CGH Array and genome wide molecular analysis may reveal additional somatic mutations not captured by standard cytogenetic analysis [7,13]. Figure 1: CDKN2A/CDKN2B gene localised in chr 9; CDKN2A encode two suppressor proteins p14ARF (exon 1α and exon 2) and p16INK4A (exon 1β, exon2 and exon 3), CDKN2B encode one protein p 15.…”
Section: Introductionmentioning
confidence: 99%